'The planners' dream goes wrong?' Questioning citizen-centred planning. Issue 3 (4th May 2017) - Lord, Alex; Mair, Michael; Sturzaker, John; Jones, Paul
ABSTRACT: The reform of urban and environmental planning in England since the election of the Coalition government in 2010 has resulted in the emergence of Neighbourhood Planning: a situation in which citizens can autonomously assemble, define the spatial extent of their neighbourhood and author a plan for it. In this paper, we argue that this radical policy is part of a wider agenda to de-professionalise planning as a statutory function and has its roots in an odd assemblage of classical right-wing political thinking and the prescriptions of post-positivist planning theory. This uneasy conceptual relationship reveals a wider inconsistency between the policy in rhetorical form and its practical implementation. Drawing on primary research from England's North-West and a thorough review of literature, we hope to show that the dream of citizen-centred planning masks deep tensions within the activity of urban and environmental management.